A ESCOLHA DA MELHOR ENTRE AS MENORES ROTAS EM REDES ÓPTICAS TRANSPARENTES - Durães, Gilvan Martins (2010)
This dissertation introduces the problem of the best choice among M combinations of the shortest paths for dynamic provisioning of lightpaths in all-optical networks. To solve this problem in an optimized way (shortest path and load balance), a new fixed routing algorithm, named Best among the Shortest Routes (Melhor entre as Menores Rotas - MMR), is proposed. The MMR s performance is compared in terms of blocking probability and network utilization to Dijkstra s shortest path algorithm and the algorithm proposed in the literature. The evaluated scenarios include several representative topologies for all-optical networking, considering networks with and without wavelength conversion capability, under uniform and non-uniform traffic load. For all the studied scenarios, MMR achieved superior performance